Dimples as Desired Outcomes: Rethinking Their Role in Thread Lifting Procedures - Kyu-Ho Yi, MD, PhD; Deborah Chua, MBChB (Plastic and Reconstructive Surgery, Global Open)
Summary:. Facial thread lifts, known for being minimally invasive with quick results, can sometimes lead to dimpling. A case report of a 35-year-old Asian man who developed a pleasing unilateral dimple after a thread lift highlights the potential for intentional dimple creation through this method. With surgical dimple creation in demand, as dimples symbolize good luck in Chinese culture and beauty in Arabic traditions, thread lifts may offer a less invasive alternative for those seeking dimples without surgery. The patient in the case report was satisfied and chose not to reduce the dimple, though further studies are needed to ensure safety and improve patient satisfaction.